Nrf2 Is a Central Regulator of Metabolic Reprogramming of Myeloid-Derived Suppressor Cells in Steady State and Sepsis - Ohl, Kim; Fragoulis, Athanassios; Klemm, Patricia; Baumeister, Julian; Klock, Wiebke; Verjans, Eva; Böll, Svenja; Möllmann, Julia; Lehrke, Michael; Costa, Ivan; Denecke, Bernd; Schippers, Angela; et al. (Frontiers in Immunology, 2018)
Arising in inflammatory conditions, myeloid derived suppressor cells (MDSCs) are constantly confronted with intracellular and extracellular ROS molecules and oxidative stress. Generating mice with a constitutive activation of Nuclear factor (erythroid-derived 2)-like 2 (Nrf2) we show a pivotal role of the anti-oxidant stress defence for development of these immune-modulatory cells. These mice are characterized by a massive increase of splenic CD11b+Gr-1+ cells, which exhibit typical suppressive characteristics of MDSCs. Whole transcriptome analysis revealed Nrf2 dependent activation of cell cycle and metabolic pathways, which resemble pathways in CD11b+Gr-1+ MDSCs expanded by in vivo LPS exposure. Constitutive Nrf2 activation thereby regulates activation and balance between glycolysis and mitochondrial metabolism and hence expansion of highly suppressive MDSCs, which mediate protection in LPS-induced sepsis. Our study establishes Nrf2 as key regulator of MDSCs and acquired tolerance against LPS induced sepsis.